On the Gauss Map of Ruled Surfaces of Type II in 3-Dimensional Pseudo-Galilean Space - Ogrenmis, Alper Osman; Ergut, Mahmut (Soc Paranaense Matematica, 2013)
In this paper, ruled surfaces of type II in a three-dimensional Pseudo Galilean space are given. By studying its Gauss map and Laplacian operator, we obtain a classification of ruled surfaces of type II in a three-dimensional Pseudo Galilean space.
Keywords: Pseudo-Galilean Space; Ruled Surfaces; Gauss Map